Concentrations of the Terrestrial Radionuclides and Their Radiological Risk at Wadi Nugrus, South Eastern Desert, Egypt - Abdel-Razek, Yassin A.; Bakhit, A. F.; Abdel-Wahab, M. M.; El-Anwar, N. I. (Universitas Sebelas Maret, 2024)
Fourteen samples were collected from a minor tributary at Wadi Nugrus, SED, Egypt. The average values of the activity concentrations of the terrestrial radionulclides U-238 and Th-232 in the studied samples were 325 and 277 (Bq/kg) much higher than the worldwide averages. The average value of K-40, 820 (Bq/kg), is comparable to the worldwide average concentration of this radionuclide. Four samples have safe values for the hazard indices Raeq, Hex and Hin. This represented a contradiction with values of the absorbed dose rate D which has a minimum value of 110 (nGy/h) exceeding the worldwide average of 60 (nGy/h). At the announced safe unity for both Hex and Hin, the total annual effective dose appears to have more than the value of 6 (mSv/y) which far exceeds the worldwide average effective dose rate of 1.5 (mSv/y). The effective dose approach established by UNSCEAR is reliable since the effective dose reacts directly with the dose limits recommended by the radiation protection regulations.